2008
DOI: 10.1213/01.ane.0000333274.63501.ff
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Randomized Trials Evaluating Regional Techniques for Postthoracotomy Analgesia

Abstract: Either thoracic epidural analgesia with LA plus opioid or continuous paravertebral block with LA can be recommended. Where these techniques are not possible, or are contraindicated, intrathecal opioid or intercostal nerve block are recommended despite insufficient duration of analgesia, which requires the use of supplementary systemic analgesia. Quantitative meta-analyses were limited by heterogeneity in study design, and subject numbers were small. Further well designed studies are required to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
355
1
26

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(391 citation statements)
references
References 79 publications
9
355
1
26
Order By: Relevance
“…Results of the analyses suggest analgesic equivalence but fewer adverse effects, such as hypotension, nausea and vomiting, urinary retention, and pulmonary complications. [1][2][3] Thus, continuous paravertebral blocks remain an attractive alternative to epidural blocks; however, the optimal approach to paravertebral analgesia is yet to be defined, and many modifications have been described, especially after the advent of ultrasound guidance.…”
Section: Résumémentioning
confidence: 99%
“…Results of the analyses suggest analgesic equivalence but fewer adverse effects, such as hypotension, nausea and vomiting, urinary retention, and pulmonary complications. [1][2][3] Thus, continuous paravertebral blocks remain an attractive alternative to epidural blocks; however, the optimal approach to paravertebral analgesia is yet to be defined, and many modifications have been described, especially after the advent of ultrasound guidance.…”
Section: Résumémentioning
confidence: 99%
“…Previous studies have suggested that local anesthetic doses for TEA should be half those of subpleural analgesia. 4,5 In the current study, the starting bolus doses were given at a ratio of 1:2, but the PCA doses were lower than the doses used in the study by Kanazi et al For supplemental therapy, paracetamol and diclofenac sodium were used in the current study. These bupivacaine doses in the TEA group were sufficient for analgesia, and reduced the rate of complications.…”
Section: Discussionmentioning
confidence: 87%
“…düzelmesine hem de komplikasyonların azaltılmasına katkıda bulunduğu bildirilmiştir (1)(2)(3) . Toraks cerrahisi sonrası analjezide rejyonal teknikler (örn, torakal epidural kateter) oldukça etkin olmasına karşın, özel beceri gerektirmesi, her hastaya uygulanamaması (kardiak hastalık, ankilozan spondilit vs) hastaların invaziv girişimi reddetmesi ve ciddi komplikasyon potansiyeli nedeniyle (hematom, infeksiyon, sinir hasarı vb.)…”
Section: Gereç Ve Yöntem: Torakotomi Yapılan 30 Hasta Randomize Olaraunclassified
“…sistemik analjeziklere kıyasla daha etkin analjezi sağladığı ve solunumsal komplikasyonları azalttığı bildirilmektedir (2,13) . Ancak, bu tekniklerin bir çoğunun, invaziv olması nedeniyle ciddi komplikasyon riski içermesi, hastaların istememesi, özel beceri gerektirmesi, bazen teknik hatalar sonucu analjezinin yetersiz kalması ve her hastaya uygulanamaması nedeniyle sistemik ilaç uygulamaları da gerekmektedir (4)(5)(6)(7) .…”
Section: Materyal Ve Metodunclassified